Early Childhood Educators' Fear of Injury Risks Limits Movement and Physical Activity for Children-A Risk in Itself! - Ann-Christin Sollerhed (MDPI AG, 2024)
Many children spend a large proportion of their waking hours in early childhood education and care (ECEC). Movement and physical activity (PA) are crucial for children's development and sustainable health. The competence to manage and assess risks starts early in life and can be improved through opportunities for challenging PA. The aim of this study was to investigate ECEC educators' experiences and perceptions of injury risks in ECEC and examine their reasoning about teaching movement and PA, and experiences of any restrictions and prohibitions of movement and PA. Eighteen ECEC educators were interviewed. The qualitative content analysis revealed three themes with adherent sub-themes: Responsibility for the children (Caretaking and Empathy); Fear of being accused (Fear of being exposed and Fear of being irresponsible in the work team); Low competence in movement (Low expectations of children and Perceived poor personal movement skills). The study concluded that educators' fear of injury risks limits the children's movement and PA occasions. The educators' perceived poor personal motor skills and low fitness combined with their perceived low competence to teach movement limit the possibility for the children to develop their motor skills, which in turn might affect the children's physical literacy for sustainable health.